Review on Polymer-Based Composite Electrolytes for Lithium Batteries - Yao, Penghui; Yu, Haobin; Ding, Zhiyu; Liu, Yanchen; Lu, Juan; Lavorgna, Marino; Wu, Junwei; Liu, Xingjun (Frontiers in Chemistry, 2019)
Lithium-ion batteries have been made on a fantastically wide range of applications. However, current commercial lithium-ion batteries extensively use low-boiling point organic liquid electrolytes, which are prone to leakage, burning and even explosions. Solid electrolyte offers one options to solve the issues. Among all solid electrolytes, polymer based solid electrolytes have the advantages of low flammability, good flexibility, excellent thermal stability, and high safety. A large amount of research work had been devoted to the realization of high performance solid polymer based lithium batteries. However, low Li-ion conductivity and poor mechanical properties still hinder the commercial applications. In order to tackle the issues and improve the overall performance, composite with foreign particles are currently widely investigated to form a polymer-based composite electrolyte. This review discusses the current developments on polymer-based composite lithium ions solid electrolytes. In particular, the structures, ionic conductivities and fabrications of solid polymer electrolytes are summarized, as well as electrochemical/chemical stabilities. And perspectives on future developments of solid polymer electrolytes are provided for future lithium ion batteries.